KONTRIBUSI SISTEM AGROFORESTRI TERHADAP PENDAPATAN PETANI HUTAN KEMASYARAKATAN (HKm) SUKA MAJU DI DESA TEBING SIRING KABUPATEN TANAH LAUT - Yulia Fitriani; Mahrus Aryadi; Muhammad Naparin (Jurnal Sylva Scienteae, 2020)
Community Forestry  is a state forest whose utilization is primarily aimed at empowering communities in and around forest areas as well as providing access to local communities in managing forests sustainably in order to ensure the availability of jobs for the local community. The form of sustainable forest management, namely with agroforestry activities. Agroforestry can improve the welfare of farmers with contributions given both  farmers and  outcome of farming results. The purpose of this study was to find out the results of income and production of rice and jengkol in the agroforestry system, knowing the amount of income contribution from the agroforestry system and knowing the problems and expectations of the community. This research was conducted in Tebing Siring Village, Bajuin District, Tanah Laut Regency. The method used in this study is descriptive method with in-depth interview techniques and field observations. The results showed that the annual agroforestry business income was Rp.17,000,000 and the smallest was Rp.600,000 while the average production of rice and Jengkol was 440 liters and 18 belek. The difference in annual agroforestry business income is very far, this is due to the lack of interest of farmers in running agroforestry businesses and ignorance of the magnitude of the profits obtained if the agroforestry business they run is successful, this results in low contributions. The highest contribution of rice and jengkol agroforestry systems was 32% and the smallest contribution was 2.4%. The average contribution was 15%. The problem faced by farmers is the presence of rat and beruk (bangkui) which causes the production and income from agroforestry decreace..Keywords : Community Forestry; Agroforestry; Contribution